2015
DOI: 10.1371/journal.pone.0135956
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Toxoplasma gondii Seroprevalence in Shelter Cats and Dogs during 1999–2001 and 2009–2011 in Tokyo, Japan

Abstract: Toxoplasma gondii is an important human health concern with respect to abortion, congenital hydrocephalus, and encephalitis in immunocompromised people. Cats and dogs both are potential sources of T. gondii because they have close contact with humans. However, no epidemiological surveys have been conducted in Tokyo over the past decade. Therefore, the present study investigated and compared the seroprevalence of T. gondii infection in shelter cats and dogs during 1999–2001 and 2009–2011 in Tokyo, Japan. Serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 20 publications
6
26
1
1
Order By: Relevance
“…The present survey showed that T. gondii seroprevalence in cats in rural areas was significantly higher compared to urban cats ( p  < 0.01), which is consistent with reports by other authors [1, 10]. The difference in seroprevalence in urban and rural areas might be explained by differences in local reservoirs of the parasite, both in prey animals and in the environment, which serve as local infection sources for the cats.…”
Section: Discussionsupporting
confidence: 91%
“…The present survey showed that T. gondii seroprevalence in cats in rural areas was significantly higher compared to urban cats ( p  < 0.01), which is consistent with reports by other authors [1, 10]. The difference in seroprevalence in urban and rural areas might be explained by differences in local reservoirs of the parasite, both in prey animals and in the environment, which serve as local infection sources for the cats.…”
Section: Discussionsupporting
confidence: 91%
“…For two pathogens with environmental transmission, T. gondii and FPV, we also predicted its prevalence to be positively associated with the PD of cats. In the case of T. gondii, the overall number of positive individuals was low in general ( Table 3 ), similar to other studies on T. gondii prevalence in urban stray cats, which ranged from 5.61 to 14.3% ( Lee et al, 2011 ; Wang et al, 2012 ; Oi et al, 2015 ). Additionally, its prevalence did not show any significant association with PD or CCA.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence varied by area of the island (5.1–19.6%). In epidemiological studies in other countries, the T. gondii antibody seroprevalence among cats in rural areas has tended to be higher than that in urban cats [ 6 , 10 ]. In our present study, there was a similar tendency.…”
mentioning
confidence: 99%